New Normal Quality of Life according to Dhamma Principle in Covid-19 Pandemic Crisis in Khwao Sinrin District Municipality, Surin Province - et. al., Phrapalad Sura Yanatharo (Chanthuek), (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study the adaptation in Covid-19 Pandemic Crisis in Khwao Sinrin district municipality, Surin province, 2) to study problems and obstacles in the adaptation in this area, and 3) to study ways to improve the quality of life in New Normal according to Buddhist principles in Covid-19 Pandemic Crisis in this area. Mixed methods research was used for research design. Quantitative research by handing out questionnaires from a sample of 375 persons. Qualitative research was used in-depth interviews with 10 key informants and the group discussion with 8 samples. The statistics used include frequency, percentage, average, and standard deviation. Results indicated that 1) the adaptation in Covid-19 pandemic crisis in Khwao Sinrin district municipality, Surin province found that people pay attention to maintaining cleanliness, refraining from unnecessary activities, and be cautious to live in carelessness. Recognizing public policy on prevention treatment and awareness of the seriousness of Covid-19, and being vigilant in social coincide and being able to advantage communication technology innovations, 2) the problems and obstacles the adaptation in this crisis found that people were concerned with the dangers and severity of pathogens, stress. People confused with many information, and 3) the ways to improve life’s qualities in new normal according to Buddhist principles in this crisis found that the self-development by having a good relationship with the environment and with others as well as to adaptation of working life with honesty and aptitude for living in a society with peacefully..